Изменение парадигмы методологии юриспруденции - Оборотов, Юрий Николаевич; Оборотов, Юрій Миколайович; Oborotov, Jurij (My University, 2013)
In modern methodology of jurisprudence there is a transition from the study the states of its object to its comprehension in changes and transformations. Hence the two subsystems of methodology of jurisprudence: subsystem facing the states of the law and the state as well as their components and aspects; and subsystem facing the changes of the law and the state in general and their constituents. These subsystems of methodology of jurisprudence receive its reflection in conceptual form, methodological approaches, methods, specific concepts. Methodology of jurisprudence should not be restricted to the methodology of legal theory. In this regard, it is an important methodological question about subject of jurisprudence. It is proposed to consider the subject of jurisprudence as complex, covering both the law and the state in their specificity, interaction and integrity. Indicative changes in the content methodology of jurisprudence are the usage of decisive importance methodological approaches that govern research strategy searches in conjunction with the law and the state. Among the most characteristic of modern development approaches: anthropological, axiological, civilization, synergistic and hermeneutic. Modern methodology of jurisprudence is pluralistic in nature alleging various approaches to the law and the state. Marked approaches allow the formation of a new paradigm methodology of jurisprudence.
Оборотов Ю. Н. Изменение парадигмы методологии юриспруденции / Ю. Н. Оборотов // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 32-40.
Keywords: методология юриспруденции; объект и предмет юридической науки; подсистемы методологии юриспруденции; методологические подходы; новая парадигма методологии юриспруденции; методологія юриспруденції; об'єкт і предмет юридичної науки; підсистеми методології юриспруденції; методологічні підходи; нова парадигма методології юриспруденції; methodology of jurisprudence; the subject of legal science; subsystem of methodology of jurisprudence; methodological approaches; a new paradigm of methodology of jurisprudence